The Last Pillar to Fall? Domestic and International Legal Institutions - Jeffrey K. Staton and Will H. Moore (My University, 2016)
The grip of Realism on the study of international politics has been considerably loosened over the past three decades, but one of the central assumptions of Realism remains un- challenged by scholars working within other approaches: the primary distinction between domestic and international politics lies in a sharp distinction between legal institutions. We propose that there is much to be learned by challenging this assumption. More specifically, we argue that the presumed difference between domestic and international legal institutions has been severely overdrawn. An examination of the institutional literature on comparative judicial politics reveals that this literature problematizes what IR scholars take for granted in domestic politics: delegation of authority to legal institutions, adverse rulings by those institutions, and government compliance with such rulings. Rather than assume that these processes simply work in the domestic setting, this scholarship demonstrates that it must be explained. Seen from this perspective, the distinction between the study of domestic and international legal institutions falls away, revealing that scholars interested in either arena are really working in a larger literature. To make this claim we review the existing work in the comparative judicial politics and international institutions literature pointing out areas of overlap, distinction, and opportunities for cross-fertilization.